2020
DOI: 10.7759/cureus.9977
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Celiac Disease in Children and Adolescents With Inflammatory Bowel Disease

Abstract: Introduction The association between inflammatory bowel disease (IBD) - particularly its two main subtypes, ulcerative colitis (UC) and Crohn’s disease (CD) - and celiac disease (CeD) has been attributed to an overlap in the mechanism of immune dysregulation that characterizes these conditions. Owing to the paucity of studies that have explored this condition in pediatric patients, we examined the prevalence of CeD in children with IBD. Materials and methods This is a cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Although the combination of CeD and IBD has been reported in children, its nature remains unclear. A study of Egyptian children found a significantly higher prevalence of CeD in those with IBD than in the general population [7]. Similar results were presented by Canova et al, who found that the prevalence of both UC and CD were significantly higher in CeD patients compared with a reference group; however, the authors noted a possible bias associated with the recruitment algorithm described below, which may be connected with misclassification.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Although the combination of CeD and IBD has been reported in children, its nature remains unclear. A study of Egyptian children found a significantly higher prevalence of CeD in those with IBD than in the general population [7]. Similar results were presented by Canova et al, who found that the prevalence of both UC and CD were significantly higher in CeD patients compared with a reference group; however, the authors noted a possible bias associated with the recruitment algorithm described below, which may be connected with misclassification.…”
Section: Discussionsupporting
confidence: 76%
“…The genetic similarity of IBD and CeD was first postulated by the identification of 4 shared risk loci: interleukin 18 receptor accessory protein, protein tyrosine phosphatase non-receptor type 2, T-cell activation guanosine triphosphate phase activating protein, and pseudouridylate synthase 10 (PUS10) [7]. These shared genetic pathways may be the reason for their possible comorbidity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations